2016
DOI: 10.1002/slct.201600020
|View full text |Cite
|
Sign up to set email alerts
|

Anion Guided Conformational Adjustments by Protonation Leading to Conformation Reversal

Abstract: As a general outline to show anion guided conformational adjustments of an uncommon conformer found in self-assembly of 2-[(5-methylthiazol-2-ylamino)-methyl]-phenol (1) and subsequent protonation leading to reversal of conformer is shown. On formation of nitrate salt (1 c) the anti conformer of 1 transformed to syn conformer. Whereas conformational adjustments in the corresponding syn conformer of the organocation of the chloride (1 a) and bromide (1 b) took place to adopt orientations that are different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Molecular conformations of pharmaceutically active molecules are considered to be potentially important in relation to molecular recognition, in particular, to their interaction with targets and biological activity. Extended research is dedicated to the problem of correlating molecular conformations in solution and in the crystalline state with the interactions with solvent, anions, or coformers. Different molecular conformations can coexist at the same experimental conditions in different solid polymorphs, , and even in the same phase (structures having high Z ′ values). As possible reasons for this coexistence of different conformers in the same solid phase one considers the effects of local environment in solution “snap-shot” on crystallization, the effect of different local intermolecular noncovalent interactions ranging from specific hydrogen bonds to van der Waals interactions, as well as optimizing packing energy of the whole crystal and minimizing mechanical stress. The latter factor becomes especially important at high pressures.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular conformations of pharmaceutically active molecules are considered to be potentially important in relation to molecular recognition, in particular, to their interaction with targets and biological activity. Extended research is dedicated to the problem of correlating molecular conformations in solution and in the crystalline state with the interactions with solvent, anions, or coformers. Different molecular conformations can coexist at the same experimental conditions in different solid polymorphs, , and even in the same phase (structures having high Z ′ values). As possible reasons for this coexistence of different conformers in the same solid phase one considers the effects of local environment in solution “snap-shot” on crystallization, the effect of different local intermolecular noncovalent interactions ranging from specific hydrogen bonds to van der Waals interactions, as well as optimizing packing energy of the whole crystal and minimizing mechanical stress. The latter factor becomes especially important at high pressures.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In some systems a conformational change in a molecular fragment has been correlated directly with a specific interaction either of the same, or another, remote site of the same molecule. In the case of furosemide, however, no straightforward correlation between a conformation and a selected type of intermolecular interaction or contact could be suggested. This is not surprising since for a very conformationally flexible molecule, with negligible energy penalty to distortion, no strong directional interactions are necessary to create a new conformation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…42 In a recent study, it was found that nitrate anions can cause conformational reversal of the thiazole unit. 43 Thiazole derivatives belong to a family of cytotoxic compounds in which anions may play an important role in the performance of such activity. 44 On the other hand, basicity associated with ions like fluoride or acetate ions deprotonates different thiourea compounds 45 and effect properties of thiazole ring.…”
Section: Reactivity Of the Positional Isomers L 1 And L 2 Towards Sol...mentioning
confidence: 99%
“…1. 17 These derivatives are prone to protonation; hence the protonated forms also can have similar conformers (C and D in Fig. 1) and one may utilize the hydrogen bonding ability of aminothiazole to stabilize any of such forms by hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the syn and anti forms of a salt will differ in the number of participating hydrogen bonds compared to the parent aminothiazole. 17 Polymorphs based on conformational adjustments of the aminothiazole unit by rotation over the intramolecular hydrogenbonded unit have been reported recently. 18 All these studies suggested the suitability of using aminothiazole as a model system to understand conformational adjustments.…”
Section: Introductionmentioning
confidence: 99%